Respuesta :
the answer is 3x+3 over x+7 . Since the fractions have the same denominator, you can focus on just the subtraction on the top. You subtract 2x from 5x and 1 from 4.
Answer:
[tex]\frac{3(x+3)}{(x+7)}[/tex].
Step-by-step explanation:
We have simplify the expression given as
[tex]\frac{(5x+4)}{(x+7)}-\frac{(2x+1)}{(x+7)}[/tex]
= [tex]\frac{(5x+4)-(2x+1)}{(x+7)}[/tex]
= [tex]\frac{(5x-2x)+(4-1)}{(x+7)}[/tex]
= [tex]\frac{3x+3}{x+7}[/tex]
= [tex]\frac{3(x+3)}{(x+7)}[/tex]
Therefore,answer is [tex]\frac{3(x+3)}{(x+7)}[/tex]